Egyptian and Sudanese folk-tales - Mitchnik, Helen; Fraser, Eric (Oxford : The University Press, 1978)
A retelling of traditional tales from the Sudan and Egypt
Keywords: Tales -- Egypt; Tales -- Sudan; Folklore -- Egypt; Folklore -- Sudan